2014
DOI: 10.1001/jamaophthalmol.2013.8175
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Geographic Atrophy on Fundus Autofluorescence and Polymorphisms ofCFH,CFB,C3,FHR1-3, andARMS2in Age-Related Macular Degeneration

Abstract: for the Spanish Multicenter Group on AMD IMPORTANCE Identification of the genetic risk factors that contribute to geographic atrophy (GA) could lead to advancements in interventional trials and/or therapeutic approaches for combating vision loss.OBJECTIVE To investigate whether single-nucleotide polymorphisms (SNPs) are associated with the presence and progression of established GA in age-related macular degeneration (AMD). DESIGN, SETTING, AND PARTICIPANTS Prospective, controlled, multicenter study of 154 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 31 publications
(42 reference statements)
5
24
1
Order By: Relevance
“…11 Monthly treatment may be associated with higher GA incidence but once the GA develops the growth rate is not significantly different from that observed in the PRN group. Two genetic studies that have recently shown that certain single nucleotide polymorphisms can affect the incidence of AMD pathologic features but not necessarily affect the progression of these features 23, 24 are consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…11 Monthly treatment may be associated with higher GA incidence but once the GA develops the growth rate is not significantly different from that observed in the PRN group. Two genetic studies that have recently shown that certain single nucleotide polymorphisms can affect the incidence of AMD pathologic features but not necessarily affect the progression of these features 23, 24 are consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…18 However, CFH variants are usually more strongly associated with increased risk of GA, and ARMS2 variants with CNV, 17,18,53,54 whereas we found a stronger effect of CFH on progression to CNV. Nevertheless, growth rate of GA was correlated with genotype at the ARMS2 SNP in two studies, 55,56 but not at the CFH (Y402H) SNP, 5557 although Caire et al 58 did not find evidence that GA growth rate was associated with variants in either locus. Overall, our results and previous work suggest that the CFH gene may be responsible for a slightly different AMD disease process than ARMS2, 2,18 and that different variants may have different effects on risk versus progression.…”
Section: Discussionmentioning
confidence: 87%
“…Given the significant prevalence of complement mutations in the AMD population, the complement cascade makes an intriguing clinical therapeutic target for non-neovascular AMD. Studies have already demonstrated that SNPs to the CFH and CFB genes contribute to the progression of GA 24. However, despite the promise that complement blockade shows for potential therapies, there have been several unsuccessful Phase I and Phase II trials of monoclonal antibodies, aptamers, receptor agonists, and a compstatin derivative which purported to modify the complement cascade.…”
Section: The Complement System and Amdmentioning
confidence: 99%